Best Answer

If: x2+7x+12 = 0

Then: (x+4)(x+3) = 0

So it follows: x = -4 and x = -3

* * * * *

True, but that is not using the quadratic formula.

According to the quadratic formula, for the equation ax2 + bx + c = 0:

x = [-b ± sqrt(b2 - 4*a*c)]/(2*a)

= [-7 ± sqrt(72 - 4*1*12)]/(2*1)

= [-7 ± sqrt(49 - 48)]/2

= [-7 ± sqrt(1)]/2

= [-7 ± 1]/2

= [-7 -1]/2 or [-7 +1]/2

=-8/2 or -6/2

= -4 or -3

Q: How do you solve x2 plus 7x plus 12 using quadratic formula?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

You can't because it is not a quadratic equation.

Solve using the quadratic formula

Using the quadratic equation formula:- x = 3.795831523 or x = -5.795831523

X= (3/5 , -2)

It can be solved by using the quadratic equation formula.

Related questions

You can't because it is not a quadratic equation.

Solve using the quadratic formula

Using the quadratic equation formula:- x = 3.795831523 or x = -5.795831523

a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28

X= (3/5 , -2)

It can be solved by using the quadratic equation formula.

The answer of the equation 2a -46a plus 252 = 0 using the quadratic formula is a = 5.25.

By using the quadratic equation formula: x = -5 and x = 3

2x2-10+7 = 0 Solving the quadratic equation using the quadratic formula will give you two solutions and they are: x = (5 - the square root of 11)/2 or x = (5 + the square root of 11)/2

Use the quadratic formula. x = -4.265564 or -0.234436

x = 7/2 and also x = -3/2 by using the quadratic equation formula.

I suggest you use the quadratic formula. In this case, a = 1, b = 5, c = 3.